Unequal chances: Family background and economic success - Bowles, Samuel; Gintis, Herbert; Osborne Groves, Melissa (Princeton Univ. Press, 2005)
Is the United States "the land of equal opportunity" or is the playing field tilted in favor of those whose parents are wealthy, well educated, and white? If family background is important in getting ahead, why? And if the processes that transmit economic status from parent to child are unfair, could public policy address the problem? Unequal Chances provides new answers to these questions by leading economists, sociologists, biologists, behavioral geneticists, and philosophers. New estimates show that intergenerational inequality in the United States is far greater than was previously thought. Moreover, while the inheritance of wealth and the better schooling typically enjoyed by the children of the well-to-do contribute to this process, these two standard explanations fail to explain the extent of intergenerational status transmission. The genetic inheritance of IQ is even less important. Instead, parent-offspring similarities in personality and behavior may play an important role. Race contributes to the process, and the intergenerational mobility patterns of African Americans and European Americans differ substantially. Following the editors' introduction are chapters by Greg Duncan, Ariel Kalil, Susan E. Mayer, Robin Tepper, and Monique R. Payne; Bhashkar Mazumder; David J. Harding, Christopher Jencks, Leonard M. Lopoo, and Susan E. Mayer; Anders Björklund, Markus Jäntti, and Gary Solon; Tom Hertz; John C. Loehlin; Melissa Osborne Groves; Marcus W. Feldman, Shuzhuo Li, Nan Li, Shripad Tuljapurkar, and Xiaoyi Jin; and Adam Swift.